Mental Health Status and Depression Among Medical Students in Mysore, Karnataka – An Untouched Public Health Issue - Manjunath, Renuka; Kulkarni, Praveen (National Journal of Community Medicine, 2013)
Background: Medical education across the globe is perceived as being inherently stressful. Studies on psychological problems such as stress, depression and anxiety among medical students have found that these disorders are under diagnosed and under treated. In this background the present study was undertaken with the objectives to assess the overall mental health status and magnitude of depression of medical students Methods: This Cross sectional study was undertaken in a private medical college in Mysore city for a period of three months involving all 211 students studying in I (first term) and II year (third term) MBBS. Goldberg’s General Health Questionnaire (GHQ-28) and Center for Epidemiological studies- Depression scale (CES-D) were used for assessing general mental health status and depression respectively. Results: Among 211 students included in the study, poor mental health status and depression was found in 25.1% and 40.8% of subjects. There was statistically significant association between poor mental health status and depression with age group of 17-18 years and year of study (1st year MBBS). Conclusion: Poor mental health status and depression was found to be high among medical students. This call for in-house counseling services and mentorship programme at medical colleges for early detection and treatment of these problems that will intern help in academic and curricular improvements.